Training in Preparing Semester Learning Plans and Lecture Contracts - Karnedi Karnedi; Natalia Fitriani (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This study aimed to evaluate two things. First, it assessed the effectiveness of the training program in improving the abilities of Postgraduate and PGPAUD students at Universitas Dharmas Indonesia in preparing Semester Learning Plans (RPS) and Study Contracts. This was done through pretests and posttests. Second, it measured student satisfaction with the training. Researchers involved 35 postgraduate and PGPAUD students. Pretests and posttests measured training effectiveness. Participant satisfaction was gauged through a structured questionnaire using a Likert scale from 1 to 5. Feedback was encouraged. The community service activity was successfully executed, and it met its objectives. A participatory-based community service program implementation method was used. The results showed that the training program was highly effective in improving competencies. All evaluated aspects demonstrated significant progress, with an overall 25% increase. Participants became more proficient in aligning curriculum with KKNI/OBE standards. They learned to formulate clear learning outcomes, design learning methods and assessments, complete lecture contracts, and integrate technology. This proves that the training strengthened their readiness to develop high-quality instructional documents for higher education. High participant satisfaction was due to relevant training content, professional delivery, active learning strategies, strong organizational support, and clear perceived benefits. In conclusion, the training greatly contributed to students' understanding of lesson plan design.